2006
DOI: 10.1007/s10534-005-1300-x
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate-mediated Iron Release from Ferritin in the Presence of Alloxan

Abstract: Release of iron from ferritin requires reduction of ferric to ferrous iron. The iron can participate in the diabetogenic action of alloxan. We investigated the ability of ascorbate to catalyze the release of iron from ferritin in the presence of alloxan. Incubation of ferritin with ascorbate alone elicited iron release (33 nmol/10 min) and the generation of ascorbate free radical, suggesting a direct role for ascorbate in iron reduction. Iron release by ascorbate significantly increased in the presence of allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…It has also been shown that oxidative stress may promote Fe release from ferritin following their oxidative attack by superoxide anion and/or hydrogen peroxide (Reif 1992). Ascorbate mediates iron release from ferritin, implying the reduction of stored ferric to soluble ferrous iron coupled with oxidation of ascorbate (Sakurai et al 2006). Our data suggest that such an effect could have occurred in our experiment.…”
Section: Discussionsupporting
confidence: 58%
“…It has also been shown that oxidative stress may promote Fe release from ferritin following their oxidative attack by superoxide anion and/or hydrogen peroxide (Reif 1992). Ascorbate mediates iron release from ferritin, implying the reduction of stored ferric to soluble ferrous iron coupled with oxidation of ascorbate (Sakurai et al 2006). Our data suggest that such an effect could have occurred in our experiment.…”
Section: Discussionsupporting
confidence: 58%
“…Dialuric acid is then readily autooxidized back to ALX establishing a redox-cycle reaction for the generation of superoxide radicals and H 2 O 2 Schulte im Walde et al 2002;Washburn and Wells 1997). Furthermore, recent studies have shown that enhanced ALX toxicity depends on the released iron from ferritin mediated by ascorbate (Sakurai et al 2006), and the involvement of oxygen on the redox cycling between ALX and dialuric acid (Brömme et al 2005). These experimental data indicate that various effectors are related to apoptotic b-cell death as a primary cause of T1DM.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism, which has been proposed already for bacterial siderophores (Halle and Meyer 1992;Andrews et al 2003) and for ferric protein species (Griesen et al 2004), involves the reduction of the ferric chelate by a physiological reducing agent, leading to the formation of the thermodynamically more labile ferrous chelate, which subsequently, or even simultaneously, may react with a suitable Fe(II) chelator (Boukhalfa and Crumbliss 2002;Mies et al 2006). The practical relevance of such redox-mediated iron release or ligand exchange reactions has been demonstrated for iron bound to the bacterial siderophores ferrioxamine B (Mies et al 2006) and pyoverdine (Greenwald et al 2007), or to ferritins (Laulhere and Briat 1993;Sakurai et al 2006) and bleomycin (Lovstad 1998). Hence, it seems reasonable to assume similar redoxmediated iron release reactions also for ferric PS.…”
Section: Introductionmentioning
confidence: 99%
“…Ascorbate is one of the primary antioxidants in plants (Noctor and Foyer 1998;Noctor 2006), and is available in the cytoplasm of plant cells at relatively high concentrations (up to the low millimolar level). Therefore, ascorbate has been used as reductant in several experiments on redoxmediated iron release (Lovstad 1998;Mies et al 2006;Sakurai et al 2006). NA was chosen as ligand, because there is strong evidence for an important role of this compound in the intracellular trafficking of iron (esp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation